Malta : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malta. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that Malta has been one of the fastest growing countries in the European Union after the crisis, because of a rapid structural rebalancing towards export-oriented services-mainly remote gaming and tourism. The authorities are now exploring new development areas around the blockchain technology. As per the authorities, domestic demand would continue to be the main driver of growth, and persistent labor market tightness might eventually put some pressure on wages and prices. They consider global protectionism as a key external risk and emphasized ongoing actions to address domestic risks related to money laundering. The report also shows that Malta's new development areas related to the distributed ledger technology present both opportunities and risks. The IMF team stresses that policies should focus on enhancing the economy's resilience, ensuring financial stability and integrity and making growth more inclusive. It is important to promote strong and inclusive growth by encouraging further labor market participation of women and elderly workers.